Teaching in the initial series of basic education: reflections on the choice of profession and professional practice - Pontes, Ana Paula Furtado Soares (2017)
This article discusses teaching initiation and the dilemmas of professional practice in the teachers' view who work in the early grades of primary education in state schools of Paraiba, where we develop an extension project. This qualitative research (ALVES-MAZZOTTI, 2002) was developed in three public schools located in the city of João Pessoa by carrying out interviews with eleven teachers. The article provides a brief discussion on teaching as a profession, and then analyzes the results in terms of characterization of the interviewed teachers, the choice of profession and professional practice. Our findings lead to the understanding that teaching has lost historical professional achievements, calling attention to the challenge of restoring teacher collegiality and the strengthening of the relationship among these peers (IMBERNON, 2000) as an important strategy in consolidating teaching as a profession.